Foreign Financial Flow and Poverty Reduction in Nigeria - Adedire-Ampitan, Adetumilara Adepeju; Sonekan, Wasiu Olasunkanmi (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examines the effect of foreign financial flows on poverty reduction in Nigeria between 1990 and 2024. Methodology: The study used annual time series data obtained from the World Development Indicators (WDI), Central Bank of Nigeria (CBN) Statistical Bulletin, and National Bureau of Statistics (NBS), and employed the Autoregressive Distributed Lag (ARDL) technique to examine the short-run and long-run relationships among the variables. Poverty reduction was proxied by per capita income, while official development assistance (ODA), remittances, and foreign direct investment (FDI) were used as measures of foreign financial flows. Inflation and infrastructural quality were included as control variables. Results and conclusion: The results show that ODA has a positive and significant short-run effect on per capita income, while its long-run effect is insignificant. Remittances exhibit weak and mostly negative effects on poverty reduction. FDI, however, has a positive and significant long-run effect on per capita income, indicating its contribution to welfare improvement. The study also reveals that inflation adversely affects per capita income, while infrastructural quality enhances welfare outcomes. The study concludes that foreign financial flows do not automatically reduce poverty in Nigeria, as their effectiveness depends on the nature of the inflows and the domestic economic environment. Implication of findings: The findings highlight the need for improved management of foreign financial inflows, macroeconomic stability, and increased infrastructural development to enhance the poverty-reducing benefits of external financial resources in Nigeria.